INTEREST GROUP COLLABORATIVE SYMPOSIUM: QUALITY CARE FOR PERSONS WITH DEMENTIA IN ASSISTED LIVING AND OTHER LTSS. (11th November 2018) - Kemp, C L; Schwartz, L; Pace, D
Abstract: Enhancing quality of life and care for persons with Alzheimer's disease and related dementias (ADRD) is critical and a priority underlying recent Alzheimer's Association recommendations. Co-sponsored by the Assisted Living (AL) and Research in Quality Care Interest Groups, this symposium includes four papers that present new data relevant to quality improvement. First, Kemp and colleagues investigate quality of life and care using longitudinal qualitative data gathered from 27 residents with dementia and their care partners from seven diverse AL communities. Perceptions and experiences of quality of life often narrowed, frequently becoming tied to care quality and an emphasis on physical needs. Next, Thomas et al. analyze data from four states to identify the characteristics of residents who live in specialized dementia care units within AL communities. Residents in specialized units were more likely to be older, white, have more commodities, and had higher death rates and hospice use, compared to those with an ADRD diagnosis living in other AL communities. Third, Zimmerman et al. use data from a seven-state study involving 280 AL residences to examine non-pharmacological practices aimed at addressing behavioral and psychological symptoms among residents with dementia. Between half to nearly all residences report using certain therapies, but data call into question actual practices and provide direction for protocol development, implementation, and evaluation. Last, Butler et al. examine palliative care use among those with ADRD using Medicaid claims and Medicare enrollment data. People with ADRD were less likely to use palliative care compared to those without a diagnosis.